2016
DOI: 10.1074/jbc.m115.685883
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Replicative Stress Response Pathways Are Associated with S Phase-specific Defects in Nucleotide Excision Repair

Abstract: Nucleotide excision repair (NER) is a highly conserved pathway that removes helix-distorting DNA lesions induced by a plethora of mutagens, including UV light. Our laboratory previously demonstrated that human cells deficient in either ATM and Rad3-related (ATR) kinase or translesion DNA polymerase (i.e. key proteins that promote the completion of DNA replication in response to UV-induced replicative stress) are characterized by profound inhibition of NER exclusively during S phase. Toward elucidating the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Consistent with this notion, several recent studies have suggested that “RPA exhaustion” is a frequent problem in cells undergoing extensive replicative stress [134,148151], including following UV exposure. Thus, it is possible that an insufficient supply of RPA in keratinocytes stressed by IGF-1R inactivation may lower the pool of RPA available for NER and ATR-CHK1 signaling.…”
Section: Effect Of Aging On Insulin-like Growth Factor-1 (Igf-1) Pmentioning
confidence: 79%
“…Consistent with this notion, several recent studies have suggested that “RPA exhaustion” is a frequent problem in cells undergoing extensive replicative stress [134,148151], including following UV exposure. Thus, it is possible that an insufficient supply of RPA in keratinocytes stressed by IGF-1R inactivation may lower the pool of RPA available for NER and ATR-CHK1 signaling.…”
Section: Effect Of Aging On Insulin-like Growth Factor-1 (Igf-1) Pmentioning
confidence: 79%
“…DNA was quantified with PicoGreen (ThermoFisher) using a TBS-380 fluorimeter (Turner Biosystems). Note that 100 ng of DNA was analyzed by slot blotting with rat anti-cisplatinmodified DNA antibody (Abcam, ab103261) as described (18).…”
Section: Quantification Of Cddp-induced Dna Adductsmentioning
confidence: 99%
“…Images were acquired using a DeltaVision Elite system (GE Healthcare). Intensity of nuclear RPA2 signals was evaluated using custom software, as described (18). At least 200 cells combined from 2 independent experiments were quantified for each condition.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations